Universality and variability of the heavy r-process element abundance pattern from a nonequilibrium approach - Blaschke, David; Röpke, Friedrich K.; Röpke, Gerd (Frontiers in Astronomy and Space Sciences, 2025)
A striking feature in the observed chemical composition of the majority of stars is the universality of the relative abundances of the heavy elements, although some outliers exist. We demonstrate that a nonequilibrium freeze-out approach provides a natural way of accounting for the typical abundance pattern and its variation. Here, we use a phenomenological method to characterize the coarse-grained distribution of heavy r-process elements in several astrophysical objects. The Lagrange parameters show only minor fluctuations when comparing different stars. Larger deviations are observed in stars with low metallicity. The variations in the Lagrange parameters for these stars are presented. The determination of the Lagrange parameters can be instrumental in identifying possible sources for the formation of heavy elements. In particular, density fluctuations are considered as a source for the production of heavy elements in the early Universe.